Complete mitochondrial genome sequence of Black Bengal goat (Capra hircus). Issue 2 (3rd July 2019) - Siddiki, Amam; Billah, Masum; Alam, Mohammad; Shawrob, Kazi Shefaul Mulk; Kumkum, Mahadia; Saha, Sourav; Chowdhury, Muntaha; Rahman, Atif H.; Stear, Michael; Khan, Mohammad K. I.; Miah, Gous; M.Mollah, AK; et al.
Abstract: The Black Bengal goat ( Capra hircus), is a native breed found in Bangladesh, popular due to its economic contribution. Here, we report the complete mitochondrial genome sequence of Black Bengal goat. The circular genome is 16, 640 bp long, comprising of 60.89% AT content. The genome contains 37 genes, consisting of 13 protein-coding genes, 22 tRNA genes, two rRNA genes, and a control region (D-loop).